Analysis of queueing systems in collaborative imaging centers: A patient-referring mechanism. Issue 5 (2nd September 2016) - Chen, Ping-Shun; Huang, Chun-Ying; Yang, Chun-Yi
Abstract: This research takes a practical hospital healthcare system as a case study. The objective of this research is to study hospital collaboration through a quantitative research methodology: queueing theory. Based on the computed tomography (CT) patient arrival rate, CT service rate and number of CT capacity, this study uses G/G/m formulas to calculate the patient waiting time and the queue length of three non-collaborative and one collaborative queue. According to the loading balance concept, this research derives the number of the CT patients needing to be referred from one hospital to another. The real-data set is used to validate the analytical solution for the collaborative patient-referring mechanism. The collaborative patient-referring mechanism has been implemented in the case hospital healthcare system and the benefits of hospital collaboration have been analyzed. In addition, this study discusses two barriers to hospital collaboration -- lack of information technology supports and different organizational cultures